Implementasi model microteaching biologi berbasis PjBL dan blended learning - Ali Sadikin; Jodion Siburian; Ferdiaz Saudagar; Robin Pratama (Jurnal Penelitian Pendidikan IPA, 2026)
The transformation of education in the era of the Industrial Revolution 4.0 and Society 5.0 requires a paradigm shift in the learning process, including in the education of prospective teachers. Twenty-first-century pedagogical skills such as critical thinking, collaboration, creativity, and digital literacy are essential competencies that future teachers must have. Microteaching as a program to improve teachers' teaching skills needs to adapt to the times. The urgency of this research is to improve the ability of prospective biology teachers to prepare themselves to teach by paying attention to collaboration, communication, creativity, and critical thinking. Therefore, researchers have developed a biology microteaching model based on PjBL (Project-Based Learning) and blended learning to improve the teaching abilities of prospective teachers. The aim of the research is to implement a model to test its effectiveness. This research uses a quantitative approach with a quasi-experimental method. This type of research is in accordance with the quasi-experimental design model, which allows researchers to evaluate the effect of interventions even without subject randomization. The focus of the research is to determine the effect of implementing biology microteaching models based on Project-Based Learning (PjBL) and Blended Learning on the teaching abilities of prospective biology teacher students. This research concludes that the implementation of the microteaching model based on Project-Based Learning (PjBL) and blended learning for Biology students at the FKIP Jambi University received a positive response.